PENGUKURAN KINERJA PERUSAHAAN MELALUI ECONOMIC VALUE ADDED (EVA) DAN (MVA) MARKET VALUE - Andhaniwati, Erry (Journal of Accounting and Strategic Finance, 2011)
Performance corporating to constitute one of prescriptive factor gets on descent of stock price because firm performance constitute to refuse fathom for investor deeping to determine stock bid price.  Economic Value Added, and Market Value Added are umpteen corporate performance grader that can be utilized by investor in assesses how well firm performance. Therefore to the effect this research is subject to be analyse influence among Economic Value Added , and Market Value Added to stock price on corporate Otomotif that go public at Indonesian Stock Exchange. That is utilized in this research is secondary data that as data Economic Value Added ,  Market Value Added and stock price on corporate Otomotif that go public at years Indonesian Stock Exchange 2002 until with year 2008. analisis's tech that is utilized is bifilar regression. Conclusion who can take from analisis's result bifilar linear regression is Economic Value Added, and Market Value Added having for to stock price, so hypothesis available influence Economic Value Added and Market Value Added to stock price tested by its truth.Keywords : Economic Value Added, Market Value Added, Stock Price